Surface hardness prediction of CrN thin film coating on AL7075-T6 alloy using fuzzy logic system - Zalnezhad, E.; Sarhan, Ahmed Aly Diaa Mohammed; Hamdi, M. (2013)
In recent years, CrN coating has been identified as one of the most promising protective layers on surfaces of tools and dies due to its excellent mechanical properties, corrosion resistance, and surface hardness. This study presents the predicting of chromium nitride (CrN) coating surface hardness on AL7075-T6 using fuzzy logic technique. First, Al7075-T6 was coated with CrN at different parameter conditions, after which the surfaces hardness of the CrN-coated specimens was measured using a micro hardness machine. Next, a fuzzy logic model was established to predict the surface hardness of CrN coating on AL7075-T6 with respect to changes in input process parameters, DC power, temperature, and nitrogen flow rate based on the trained data obtained from the micro hardness test. Three membership functions were allocated in connection with each model input. Finally, five new experimental tests were carried out to verify the predicted results achieved via the fuzzy logic model. The results indicate an agreement between the fuzzy model and experimental results with 94.664 accuracy.